La construcción social de las normas morales - Heler, Mario (ARFIL y UNL, 2018)
In present times, social changes affect our ethos; it is a time plenty of issues and disputes on traditional ethical conceptions as well as on present ones which try to give ethical responses to new situations. With the aim of exploring a possibility of thinking our present, I will here try to explore the interpretation matrix with which modern ethos has been articulated, and which -with some modifications- still finds its way into present times. Starting from this precision, I will move forward along a route of inquiry which opens up to us when we do not place ourselves from the point of view of “God’s eye”, i.e., when we cease to focus our reflections on what I have called the theological problem of modernity, and instead deal with the problem of the social construction of moral norms. The attempt to give reason of a secular moral position -freed from the presuppositions of the beginnings of modern times- will lead to the distinction between moral, understood as a human group’s customs and habits and ethics as the critique of established moral. I will hold that the construction of moral norms comes into play in the tension between moral and ethics.